Economic Valuation of Sufficient and Guaranteed Irrigation Water Supply for Paddy Farms of Guilan Province - Mehdi Hatami; Ali Nazemi; Azam Dowlatabadi; Mostafa Mostafapour (Rāhburdhā-yi tusi̒ah-i rūstāyī, 2014)
According to TAVANIR company`s statistics, despite fulfilling the electricity supply plans to the villages with more than 20 families in rural areas of Iran, Still, more than 17,000 rural families in villages ,with populations less than 20 families, are deprived from accessing to  the electricity. Production Losses, transmission and distribution of electricity and the distribution of the population cause use of solar energy in remote areas.  Hence, photovoltaic systems, because of direct conversion of solar energy into electricity without the need for sophisticated equipment are important. In this paper, an economic evaluation of Off Grid photovoltaic systems against national power grid has been studied in Tehran villages, due to the uncertainty in modeling; Monte Carlo simulation with 2000 iterations was used.  We did Economic evaluation, using the life cycle cost of a photovoltaic system for a period of 25 to 30 years as well as the development costs for the power grid to remote villages. The paper shows the minimum distance of the village distribution network that the photovoltaic system is more economical than the national power grid development. This distance has inverse relation with discount rate as well as direct relation with the number of cloudy days and the number of rural families.